Mismatching between circulating strains and vaccine strains of influenza: Effect on Hajj pilgrims from both hemispheres. Issue 3 (3rd March 2016) - Alfelali, Mohammad; Khandaker, Gulam; Booy, Robert; Rashid, Harunor
Abstract: The trivalent seasonal influenza vaccine is expected to provide optimum protection if the vaccine strains match the circulating strains. The effect of worldwide mismatch between the vaccine strains and extant strains on travelers attending Hajj pilgrimage is not known. Annually 2-3 million Muslims coming from north and south hemispheres congregate at Hajj in Mecca, Saudi Arabia, where intense congestion amplifies the risk of respiratory infection up to eight fold. In order to estimate, to what extent mismatching increases the risk of vaccine failure in Hajj pilgrims, we have examined the global data on influenza epidemiology since 2003, in light of the available data from Hajj. These data demonstrate that globally mismatching between circulating and vaccine strains has occurred frequently over the last 12 years, and the mismatch seems to have affected the Hajj pilgrims, however, influenza virus characteristics were studied only in a limited number of Hajj seasons. When the vaccines are different, dual vaccination of travelers by vaccines for southern and northern hemispheres should be considered for Hajj pilgrims whenever logistically feasible. Consideration should also be given to the use of vaccines with broader coverage, i.e., quadrivalent, or higher immunogenicity. Continuous surveillance of influenza at Hajj is important.